PENYULUHAN GURU-GURU SEKOLAH MENENGAH TENTANG GANGGUAN MUSKULOSKELETAL PADA REMAJA - Marpaung,SpPros.,PhD, Carolina Damayanti; Hanin, Isya; Anggraini, Wita; Juliawati, Mita; Ranggaini, Dewi; Krisna, Yohanes; Michelle, Michelle; Putri, Ni Luh (Universitas Trisakti, 2024)
Musculoskeletal disorders are common issues that affect various age groups, including children and adolescents. In dentistry, a frequently encountered musculoskeletal disorder is temporomandibular disorder, which can significantly impact the quality of life of those affected. Schools play a crucial role in preventing and detecting musculoskeletal disorders among students. However, the literature indicates that teachers' knowledge regarding musculoskeletal disorders generally remains relatively low. Therefore, education and training programs must enhance teachers' understanding of these issues. As part of its commitment to health education, the Community Service Team (PkM) of Universitas Trisakti conducted an awareness program for 100 secondary school teachers at IPEKA Tomang. The program was carried out in two stages, focusing on general musculoskeletal and orofacial disorders. The evaluation results showed an improvement in teachers' understanding of both topics, which is expected to contribute to the prevention and early management of musculoskeletal disorders in schools.